Primary Nasocutaneous Fistulae in Granulomatosis With Polyangiitis: A Case Series and Literature Review. Issue 1 (January 2021) - Bahrami, Bobak; Curragh, David; McNab, Alan A.; Davis, Garry; Dolman, Peter J.; Selva, Dinesh
Abstract : Purpose: To report the presentation, investigation, management, and outcomes of primary nasocutaneous fistulae in granulomatosis with polyangiitis and review the literature of this complication. Methods: Retrospective series of 5 patients with granulomatosis with polyangiitis and nasocutaneous fistulae and the medical and surgical management strategies employed. Results: Two cases presented with fistulae as the primary symptom of their systemic disease. Systemic management of granulomatosis with polyangiitis is a primary concern and two cases had inadequate control at presentation such that surgical intervention was deferred. Of the other 3 cases, 2 were closed using a median forehead flap and the other with an orbicularis advancement flap. An endonasal approach was attempted in 1 case but was unsuccessful due to the friable nature of the nasal mucosal tissue. Conclusions: Nasocutaneous fistulae should alert the clinician to underlying granulomatosis with polyangiitis, which may be a presentation of this condition. Systemic management of disease is often a barrier to surgical management. Myocutaneous flaps may be the most reliable management option to achieve closure. Abstract : This case series of primary nasocutaneous fistulae in granulomatosis with polyangiitis reviews the literature for this rare complication and describes potential surgical management that may be utilized to close these defects.